2018
DOI: 10.1186/s12886-018-0685-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy between anti-vascular endothelial growth factor (VEGF) and laser treatment in Type-1 and threshold retinopathy of prematurity (ROP)

Abstract: BackgroundRetinopathy of Prematurity (ROP) is one of the most common causes of childhood blindness worldwide. Comparisons of anti-VEGF and laser treatments in ROP are relatively lacking, and the data are scattered and limited. The objective of this meta-analysis is to compare the efficacy of both treatments in type-1 and threshold ROP.MethodsA comprehensive literature search on ROP treatment was conducted using PubMed and Embase up to March 2017 in all languages. Major evaluation indexes were extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 49 publications
2
38
0
2
Order By: Relevance
“…VEGF is a glycosylated mitogen that specifically affects endothelial cells and has various effects, including mediating increased vascular permeability, inducing angiogenesis, vasculogenesis, and endothelial cell growth, promoting cell migration, and inhibiting apoptosis [2224]. VEGF additionally mediates vascular endothelial permeability and proliferation [25]. In the present study, the fluorescence intensity, protein expression, and mRNA expression of VEGF in the high-sugar stimulus group were higher compared with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…VEGF is a glycosylated mitogen that specifically affects endothelial cells and has various effects, including mediating increased vascular permeability, inducing angiogenesis, vasculogenesis, and endothelial cell growth, promoting cell migration, and inhibiting apoptosis [2224]. VEGF additionally mediates vascular endothelial permeability and proliferation [25]. In the present study, the fluorescence intensity, protein expression, and mRNA expression of VEGF in the high-sugar stimulus group were higher compared with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…22 A meta-analysis that compared the efficacy of anti-VEGF agents versus laser treatment in type 1 and threshold ROP determined that laser treatment would be more effective than intravitreal injection with anti-VEGF agents. 39 In addition, the meta-analysis suggested that laser can cause more eye complications and myopia in the future. 39 It is necessary to keep in mind that treatment with bevacizumab and other anti-VEGF agents can present some complications such as recurrence of proliferative retinopathy, hyphema, vitreous hemorrhage, endophthalmitis, retinal detachment, and cataract (1%).…”
Section: Treatment With Anti-vegf Agentsmentioning
confidence: 99%
“…39 In addition, the meta-analysis suggested that laser can cause more eye complications and myopia in the future. 39 It is necessary to keep in mind that treatment with bevacizumab and other anti-VEGF agents can present some complications such as recurrence of proliferative retinopathy, hyphema, vitreous hemorrhage, endophthalmitis, retinal detachment, and cataract (1%). 40 However, the most important potential side effect is the transient decrease in serum levels of VEGF that may be different depending on the anti-VEGF agent used.…”
Section: Treatment With Anti-vegf Agentsmentioning
confidence: 99%
“…Laser photoablation of the peripheral retina is an effective treatment for APROP located in zone 1 [ 8 ]. A meta-analysis showed that laser therapy for type 1 and threshold retinopathy of prematurity (ROP) may cause more eye complications and higher myopia than anti-VEGF therapy [ 9 ]. The role of vascular endothelial growth factor (VEGF) in ROP pathogenesis has been demonstrated previously, and anti-VEGF treatments represent another therapeutic option.…”
Section: Introductionmentioning
confidence: 99%